2010
DOI: 10.1371/journal.pone.0011541
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAome of Porcine Pre- and Postnatal Development

Abstract: The domestic pig is of enormous agricultural significance and valuable models for many human diseases. Information concerning the pig microRNAome (miRNAome) has been long overdue and elucidation of this information will permit an atlas of microRNA (miRNA) regulation functions and networks to be constructed. Here we performed a comprehensive search for porcine miRNAs on ten small RNA sequencing libraries prepared from a mixture of tissues obtained during the entire pig lifetime, from the fetal period through ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
121
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(141 citation statements)
references
References 50 publications
19
121
0
Order By: Relevance
“…Using various experimental methods, certain miRNAs were continuously reported in recent studies in the field of animal embryogenesis [26,27,28,29,30]. During the implantation period, potential regulators of endometrial receptivity include miRNAs [31].…”
Section: Discussionmentioning
confidence: 99%
“…Using various experimental methods, certain miRNAs were continuously reported in recent studies in the field of animal embryogenesis [26,27,28,29,30]. During the implantation period, potential regulators of endometrial receptivity include miRNAs [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, such approaches were limited in their ability to detect rare miRNAs, or tissue-specific miRNAs from tissues that are difficult to obtain. In mammals, temporal and spatial changes in miRNA expression have been well characterized to delineate the miRNA transcription of different tissues at different developmental stages (Li et al 2010) or in different species (Li et al 2012). At the same time, one study clearly demonstrated that levels of miRNAs in serum are stable, reproducible, and consistent among individuals of the same animal species .…”
Section: Introductionmentioning
confidence: 99%
“…After filtering out low quality data which did not meet the criteria previously developed [25,26], we obtained 5.03, 9.83, 7.26 M clean data from each library, which are refered to as "mappable reads". As in other tissues, various kinds of small non-coding RNAs as well as miRNAs may also contribute to the gene regulation during the spermatogenesis process.…”
Section: Summary Of the Sequencing Results In Three Librariesmentioning
confidence: 99%
“…As described in Liu's previous study of miRNA profiling using deep sequencing [25,26], the bioinformatics pipeline was carried out with the newest version with certain improvements. All the raw reads were modified by the combination of Illumina's Genome Analyzer Pipeline software along with self-developed ACGT-102 miR program (LC Sciences).…”
Section: Sample Collectionmentioning
confidence: 99%